Effect Of Annealing Temperature On Cerium Oxide Thin Films Grown By DC Sputtering Method - Ainita Rozati Mohd, Zabidi; Hassan, Zainuriah; Lim, Way Foong (2020)
The cerium thin films were deposited on n-type Si (100) substrate by direct current (DC) sputtering followed by post-annealing at different temperature (400ᵒC and 600ᵒC, 800ᵒC, 1000ᵒC) in an oxygen ambient. In this study, the effect of annealing temperature on the crystallized CeO2 thin films was characterized by using grazing incidence X-ray diffraction (GIXRD). The surface topology and surface morphology of the CeO2 were analyzed by using atomic force microscopy (AFM) and field emission scanning electron microscope (FESEM). The energy bandgap was calculated from the ultraviolet-visible spectroscopy (UV-Vis) measurement. GIXRD result shows (111) plane has the highest peak intensity, therefore (111) plane was selected as the preferred orientation for CeO2 thin films. AFM results reveal the root-mean-square (RMS) roughness of the CeO2 thin films decreased as annealing temperature increased from 400ᵒC to 1000ᵒC